2017
DOI: 10.1007/s12471-017-1066-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the STENTYS self-apposing bare metal and paclitaxel-eluting coronary stents for the treatment of saphenous vein grafts (ADEPT trial)

Abstract: AimsTo describe the safety and performance of STENTYS self-expandable bare metal stents (BMS) versus paclitaxel-eluting stents (PES) in saphenous vein grafts (SVGs).Methods and ResultsA randomised controlled trial was performed in four hospitals in three European countries between December 2011 and December 2013. Patients with de novo lesions (>50% stenosis) in an SVG with a diameter between 2.5–6 mm were included. Primary endpoint was late lumen loss at 6 months. Secondary endpoints included procedural succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…38 No difference was observed between the two different types of stents, however, the STENTYS self-expanding stent was noted to be safe and effective. 38 In contrast, the sirolimus eluting SPARROW stent has been shown to significantly decrease late lumen loss in small coronary arteries when compared to the bare metal SPARROW stent at 8 months indicating a potential for a lower rate of restenosis. 39 4.1.2 | Shape memory polymer stents Current polymeric stents, Igaki-Tamai and DESolve, still require deployment with the addition of balloon expansion although their shape memory effect does afford them some self-expanding capabilities.…”
Section: Coronary Stentsmentioning
confidence: 95%
“…38 No difference was observed between the two different types of stents, however, the STENTYS self-expanding stent was noted to be safe and effective. 38 In contrast, the sirolimus eluting SPARROW stent has been shown to significantly decrease late lumen loss in small coronary arteries when compared to the bare metal SPARROW stent at 8 months indicating a potential for a lower rate of restenosis. 39 4.1.2 | Shape memory polymer stents Current polymeric stents, Igaki-Tamai and DESolve, still require deployment with the addition of balloon expansion although their shape memory effect does afford them some self-expanding capabilities.…”
Section: Coronary Stentsmentioning
confidence: 95%
“…The stent is available as bare-metal stent and drug-eluting stent (paclitaxel or sirolimus). Since apposition is possible in large and variable vessel diameters of, for example, proximal and distal main branches, the stent can be used safely and effectively in bifurcation lesions [ 7 9 ] and in saphenous vein grafts [ 10 ]. Moreover, the nitinol platform can enlarge further after implantation.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia, venous hypertension, and decreased sheer force of blood flow are important factors leading to the initiation of varicose venous inflammatory response. The study of Ijsselmuiden et al [28] found that perfusion of hypoxic solution into the vein can cause adhesion reaction between neutrophils and endothelial cells, suggesting that a certain degree of decrease in blood oxygen partial pressure, such as during blood stasis, can cause activation of vascular endothelial cells. Moreover, the enhanced adhesion reaction between neutrophils and endothelial cells promoted the production of reactive oxide species (ROS) caused the release of multiple cytokines, leukotriene B4, and other inflammatory mediators.…”
Section: Related Work a Overview Of Varicose Veins Of The Lower mentioning
confidence: 99%